Morphological and functional indicators of 10-13 year-old adolescents with the scoliosis of I-II degree - Anastasia Podolyaka; Oleg Podolyaka; Ruslan Iskandarov (Kharkiv State Academy of Physical Culture, 2017)
Purpose: to study the features of morphological and functional indicators of 10-13 year-old adolescents suffering with the scoliosis of I-II degree, to determine the main directions in the preparation of comprehensive rehabilitation programs for improving posture in children. Material & Methods: based on the analysis of the specialized literature and the generalization of the obtained data of the conducted study of 42 school-age children, which are divided into two groups - the basic (with scoliosis deformation of the spine) and the control (practically healthy children of the same age), the main directions for the compilation of comprehensive rehabilitation programs. Results: It established the fact of violations of the cardiovascular and respiratory systems in children with scoliosis. Indicators of boys and girls have different directions. Conclusion: preparation of corrective programs requires not only the formation and consolidation of the habit of correct posture, the creation of a muscular corset, but also the focus on improving the development of a cardiovascular and respiratory systems with a special approach to children of different sexes.